2016
DOI: 10.21010/ajtcam.v14i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Bi̇ologi̇cal and Phytochemi̇cal İnvesti̇gati̇ons of Extracts From Pterocarpus Eri̇naceus Poi̇r (Fabaceae) Root Barks

Abstract: Background: Pterocarpus erinaceus Poir. belonging to Fabacae familly is used as medicinal plant in Burkina Faso's folk medicine.Roots of P. erinaceus are used to treat ulcer, stomach ache and inflammatory diseases. The objective of the present study was to carry out phytochemical composition of methanol (MeOH) and dichloromethane (DCM) extracts from Pterocarpus erinaceus roots, to isolate pure compounds, and to evaluate their pharmacological activities. Methods:Chromatographic fractionation led to the isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Alcoholic extracts of flowers, bark, and wood demonstrated anti-diabetic effect. Numerous studies have been conducted on the anti-inflammatory activities of phytochemicals found in the genus Pterocarpus. These findings are consistent with the plant’s traditional use in the treatment of inflammation and boils . Only one report was found about the anti-inflammatory activity of the bark; however, nothing has been reported about the biological activity and compounds of Andaman padauk fruits.…”
Section: Introductionmentioning
confidence: 72%
“…Alcoholic extracts of flowers, bark, and wood demonstrated anti-diabetic effect. Numerous studies have been conducted on the anti-inflammatory activities of phytochemicals found in the genus Pterocarpus. These findings are consistent with the plant’s traditional use in the treatment of inflammation and boils . Only one report was found about the anti-inflammatory activity of the bark; however, nothing has been reported about the biological activity and compounds of Andaman padauk fruits.…”
Section: Introductionmentioning
confidence: 72%
“…18 Other authors also report that antioxidant substances can prevent and delay lipid oxidation by acting on the reduction of ROS and the production of other free radicals. 19 The antiradical activity of the extracts varied between 7.29 ± 0.61 and 43.31 ± 0.25 µg/mL and 2.69 ± 0.25 µg/mL for gallic acid. Recurrently, the hydroethanolic extracts gave the best antiradical activities.…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 95%
“…The widespread use of some of these plant species could be related to the chemical Diseases/Ailment Recorded compounds they contain (such as sterols, carbohydrates, proteins, amino acids, alkaloids coumarins, saponins, tannins, flavonoids, phenols, and saponins) and/or their antimicrobial, digestive or laxative capacity. These chemicals are also known to have important anthelmintic activities or contribute to healing of the ailments mentioned above (Akinpelu et al 2009;Aliyu and Chedi 2010;Noufou et al 2016;Ouachinou et al 2019).…”
Section: Plant Partsmentioning
confidence: 99%